Histidyl-Transfer Ribonucleic Acid Synthetase in Positive Control of the Histidine Operon in Salmonella typhimurium - Wyche, James H. (1974)
Histidyl-transfer ribonucleic acid (tRNA) synthetase (HRS), coded by the hisS gene, appears to play two roles in regulation of the histidine operon of Salmonella typhimurium: (i) in synthesis of a critical effector molecule, histidyl-tRNA, and (ii) a more direct effect elicited by the presence of the enzyme protein itself. The specific activity of HRS was elevated either by mutations in the strB locus or in hisS(+) merodiploids of Escherichia coli/S. typhimurium and S. abony/S. typhimurium. In each case, an increase in HRS was accompanied by an increase in histidine operon expression, indicating that HRS may be involved in positive control of the histidine operon. It is unlikely that HRS leads to increased histidine operon expression merely by acting as a “sponge” for charged tRNA. Rather, HRS appears to influence operon expression by interaction with some effector molecule other than charged tRNA or by a direct interaction with the histidine operator-promoter region. The functional level of histidine operon expression has no effect on HRS specific activity.